Repeated‐batch fermentation of L‐lactic acid from acid hydrolysate of sweet sorghum juice using mixed neutralizing agent under unsterilized conditions. Issue 7 (6th February 2017) - Wang, Yong; Chang, Jingqiang; Cai, Di; Wang, Zheng; Qin, Peiyong; Tan, Tianwei
Abstract: BACKGROUND: Efficient bioconversion of biomass‐derived sugars and a mild process under unsterile conditions are key challenges for an economically and sustainably feasible process for L‐lactic acid fermentation. The open repeated‐batch fermentation of L‐lactic acid from sweet sorghum juice using mixed neutralizing agent is reported for the first time. RESULTS: With the optimized mode of neutralizing agent addition (60 g L −1 sodium lactate and 40 g L −1 calcium lactate) and acid hydrolysate of sweet sorghum juice and yeast extract and salts medium, the L‐lactic acid titer, yield and productivity reached 102 g L −1, 0.942 g g −1 and 2.90 g L −1 h −1, respectively. Furthermore, corn steep powder substituting yeast extract and salts proved to be an efficient supplement to acid hydrolysate of sweet sorghum juice in this process. CONCLUSION: Based on sweet sorghum juice, an open repeated‐batch fermentation process of L‐lactic acid using mixed neutralizing agent was developted. The good stability in long‐term operation over five batch fermentations indicates an efficient way of L‐lactic acid production from sweet sorghum juice. © 2017 Society of Chemical Industry